Pump angle and position effects on laser emission from quasicrystal microcavity by nine-beam interference based on holographic polymer-dispersed liquid crystals. Issue 3 (19th February 2018) - Li, Yong; Du, Qingguo; Liu, Zongdai; Chen, Rui; Dai, Haitao; Luo, Dan
ABSTRACT: We demonstrate pump angle and position effects on lasing from all organic quasicrystal fabricated by nine-beam interference. The output wavelengths of lasing are experimentally investigated with different pump angles. The underlying mechanism is explained by the photonic band edge simulated by finite-difference time-domain method. Additionally, the position effect on lasing is also demonstrated, and the emission characteristics of lasing are studied. The mirrorless laser is featured by low cost, and simple fabrication, which enables quasicrystal based on holographic polymer-dispersed liquid crystal an all organic miniature lasing devices. GRAPHICAL ABSTRACT: